A bizarre case report of self-harm by ingested lock trapped in oropharynx - Haque, Mohd Asrarul; Hussain, Munawwar; Usmani, Jawed Ahmad (International Journal of Research in Medical Sciences, 2017)
The present case report deals with a highly and yet unreported case of self-harm in which a medium sized lock was ingested with convulsive movements of the face and neck which ultimately got trapped in oropharyngeal region. The lock managed to ‘sink’ and settled down in that region so that the patient did not feel any gross pain once it was swallowed. There was history of mental illness reported by the attendants of the patient that remained unverified since no treatment card or the name of drug(s) was shown to the treating team of doctors. Therefore, it remained speculative whether the attempt to swallow lock was as a result of psychiatric illness or was supplemented by other social factor notable the influence of “Tantrik”. Tantriks are special breed of spiritual healers who resorted to unscientific method of healing. At times they use unethical practices. There are reports in which tantrik have provoked their unsuspecting victims to highly complex maneuvers leading to self-harm. The present case, it is believed falls in this category.